MO129: Influence of Menstrual Situation on the Risk of Incident Microalbuminuria in School Workers: Miyagi Karoshi Prevention Study. (3rd May 2022) - Munakata, Masanori; Hattori, Tomomi; Konno, Satoshi; Kubota-Nakayama, Fumie; Inoue, Nobutaka; Nakamura, Tomohiro; Hozawa, Atsushi
Abstract: BACKGROUND AND AIMS: It has been recognized that menstrual situation impairs diagnostic accuracy of proteinuria. However, it is not fully understood how menstrual situation affects the degree of urinary albumin excretion, a well-known marker of endothelial damage. Moreover, there may be no report examining the dose–response relationship between contaminated blood and the risk of incident microalbuminuria. METHOD: We studied 735 female school staffs (40.6 ± 11.2 years) who participated in the Miyagi Karoshi Prevention study. Urinary albumin excretion adjusted for creatinine (UAE) from morning spot urine sample was examined together with annual health check-up in 2019 and 2020. Menstrual situation was confirmed by a questionnaire at the time of examination. First of all, we examined the odds ratio for microalbuminuria of menstruation by means of logistic regression analysis using baseline data of 703 subjects with normo-albuminuria (NA) and 32 subjects with micro-albuminuria (MA). Next, we examined the dose–response relationship between urine blood category of − (n = 49), ± (n = 13 ), + (n = 22), 2+ (n = 13), 3+ (n = 47) and UAE or frequency of MA in 144 non-diabetic, non-hypertensive subjects without chronic kidney disease who were menstrual and non-menstrual situation in either year. RESULTS: Age and BMI were similar between MA and NA groups, while frequency of menstruation (31.2 versus 15.4%, P < .05), hypertension, or BP ≧ 140/90 mmHg or use of antihypertensive medications (34.4 versus 10.0%, P < .001) and diabetes, or HbA1c ≧ 6.5% or use of antidiabetic medications (9.4 versus 2.3%, P < .05) was higher in MA than in NA group. Multivariate logistic regression analysis has shown that MA was significantly associated with menstruation (OR 2.65: 95% CI 1.17–53.99) and hypertension (OR 4.41: 1.69–11.51). UAE was dose-dependently increased with an increase in urine blood category ( P < .001). Frequency of MA in each urine blood category was 0.0, 4.5, 0 and 17.0% ( P = .001), respectively. CONCLUSION: Contamination of blood into urine dose-dependently increases UAE in menstruated women. The diagnosis of MA may be possible even in menstrual situation if urine blood category is 2+ or lower.